Nursing Students' Tendency To Aggression and Relevant Factors - CAN GÜRKAN, ÖZLEM (KARE PUBL, 2016)
Objectives: The objective is to evaluate tendencies to aggression among nursing students and to analyze the risk factors that may increase the aggression. Methods: The population of our descriptive and cross-sectional study consists of 350 students studying at the department of nursing of a university in Istanbul. Sampling includes 236 students who are representative of the population, are 18 years or older, and were selected with the basic random sampling method. All volunteered to participate in the study. The data were obtained using the questionnaire form and the Aggression Scale, and the self-rating method was used to obtain data. Statistical data analysis was performed using chi-square test, Mann-Whitney U-test and logistic regression analysis. Results: The aggression scores of the males whose mothers were exposed to physical violence by their fathers, who were exposed to physical violence by their mothers and fathers, and who used physical violence were found statistically more significant. As a result of the logistic regression analysis, being exposed to physical violence by the mother, using physical violence, being a male, having a father who uses physical violence against the mother, mother's and father's educational status of primary school and having two or more siblings are specified as certain risk factors for the high tendency to aggression. Conclusion: Considering the outcomes of the study, we recommend that education programs be prepared in order to evaluate nursing students in terms of these risk factors, and for nursing students who display a high tendency toward aggression.
Keywords: Nursing students; aggression; factors related to aggression; violence; HIGH-SCHOOL-STUDENTS; INTIMATE PARTNER VIOLENCE; DOMESTIC VIOLENCE; FAMILY VIOLENCE; BEHAVIOR; PERPETRATION; PREVALENCE; EXPOSURE; CHILD; ANGER